2018
DOI: 10.1111/jopy.12427
|View full text |Cite
|
Sign up to set email alerts
|

Leaders’ achievement goals predict employee burnout above and beyond employees’ own achievement goals

Abstract: We advance our understanding of the motivational etiology of burnout by examining the top-down effects of leaders' achievement goals on employee burnout over and above employees' own achievement goals. In order to reduce burnout, organizations should take leaders' achievement goals into account as an important contextual factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 60 publications
0
18
0
1
Order By: Relevance
“…Thus, employees engaged in OCB will benefit from the social support and positive relationships within an organization to mitigate their burnout. Recent studies have identified that support of others (i.e., colleagues) in the organization and the effective leadership by supervisors can play a key role in burnout manifestation and its effect on individuals (e.g., turnover intentions) and organizations [126,127]. Therefore, when employees engage in OCB, this is beneficial not only for the organizations, but also for individuals themselves.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Thus, employees engaged in OCB will benefit from the social support and positive relationships within an organization to mitigate their burnout. Recent studies have identified that support of others (i.e., colleagues) in the organization and the effective leadership by supervisors can play a key role in burnout manifestation and its effect on individuals (e.g., turnover intentions) and organizations [126,127]. Therefore, when employees engage in OCB, this is beneficial not only for the organizations, but also for individuals themselves.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Our propositions align with these recent findings on how high LGO employees behave at work, but instead we focus on the consequences of these behaviors during non-work time. In doing so, we extend what is currently understood about LGO because this concept has been treated as uniformly beneficial (for a recent example, see Sijbom, Lang, & Anseel, 2019). Such understanding is valuable because it provides space, and prompts research to examine the true nature and consequences of LGO more critically than has been done so far.…”
Section: Introductionmentioning
confidence: 86%
“…Leaders' performance-approach goal (α = 0.93) and leaders' mastery-approach goal (α = 0.79) were measured using the corresponding three-item subscales of the Achievement Goal Questionnaire-Revisited (AGQ-R; Elliot et al, 2011). Items were adapted to fit the work context of the research by changing the domain from a class setting ("In my classes") to a work setting ("In my work"; for similar adaptations see Sijbom et al, 2015b;Sijbom et al, 2019). Participants rated three items for the performance-approach goal construct (e.g., "My aim is to outperform other colleagues in my work") and three items for the mastery-approach goal construct (e.g., "My aim is to perform better in my work than I have done in the past").…”
Section: Methodsmentioning
confidence: 99%